Predicting the outcome of cytoreductive surgery in patients with advanced ovarian cancer - M. G. Yakovleva; T. V. Gorodnova; Kh. B. Kotiv; O. A. Smirnova; O. E. Lavrinovich; N. A. Mikaya; Yu. N. Trifanov; K. D. Guseynov; E. V. Bakhidze; I. E. Meshkova; A. S. Khadjimba; K. S. Kozyreva; et al. (ABV-press, 2023)
Background. More than 80 % of cases ovarian cancer are detected at stage III-IV. One of the most important predictive factors is the cytoreductive surgery without residual tumor.   Aim. To determine the selection criteria for cytoreductive surgery in the advanced ovarian cancer patients.   Materials and methods. The study included 190 primary IIB-IV stage ovarian cancer patients who underwent surgical treatment in the oncogynecological department of the N. N. Petrov NMRC on Oncology in the period from August 2017 to August 2020. All patients underwent pelvic magnetic resonance imaging, chest and abdominal computed tomography, and diagnostic laparoscopy. Assessment of the peritoneal carcinomatosis index (PCI) was performed according to P. Sugarbaker. The outcome of cytoreductive surgery was determined by the size of the residual tumor: complete - without a macroscopically detectable tumor, optimal - residual tumor ≤1 cm, suboptimal - residual tumor ≥1 cm.   Results. The complete or optimal cytoreduction achieved in 72.6 % of cases (48.9 % (93 / 190) and 23.7 % (45 / 190), respectively), suboptimal in 22 % (42 / 190) of cases, 5 % (10 / 190) only a diagnostic laparoscopy due to the initial underestimation of the tumor dissemination. In the entire sample PCI value ranged from 0 to 35 points, the median was 4 points (2; 11). In the group of optimal cytoreductions PCI ranged from 0 to 19 points, median - 3 points (2; 6), in the group of suboptimal from 5 to 35 points, median - 19.5 points (15; 23) (p < 0.0001, Mann-Whitney test). No optimal cytoreduction was performed in PCI >20 points. The optimal cut-off PCI point was 9.5 points (sensitivity 92.1 %, specificity 86.2 %, overall accuracy 87.4 %), if PCI ≤ 9 points - the operation will be hypothetically optimal, if PCI ≥ 10 then hypothetically suboptimal. The main cause of non-optimal interventions (n = 52) were: diffuse carcinomatosis of the small bowel and its mesentery - 73 % (38 / 52), carcinomatosis of the hepatoduodenal zone - 9 % (5 / 52) and a total of 16 % (9 / 52) were other non-resectable tumors (paraaortal, intrathoracic lymph nodes, invasion of the pancreas or pleura, lung metastases). Radiation diagnostic and intraoperative revision were comparable in 60.5 % (115 / 190) of cases. The sensitivity of radiological diagnostic methods in detecting of the small intestine lesions was 23.7 %, the specificity was 90 %, while for laparoscopic diagnostics, the sensitivity in detecting of the small intestine lesions was 93.3 %, and the specificity was 100 %. In assessing of carcinomatosis of the hepatoduodenal zone, the advantage belongs to radiation diagnostic methods: the sensitivity of computed tomography was 66.7 %, the specificity was 97 %, while the sensitivity of diagnostic laparoscopy was 0 %.   Conclusions. Determination of a high score in assessing the index of peritoneal carcinomatosis, detection of damage to the hepatoduodenal zone, diagnosed mainly by radiation imaging methods, detection of diffuse lesions of the small intestine, determined mainly by laparoscopic diagnosis reduces the frequency of suboptimal cytoreductive operations from 67 % to 13 %.